Plasmonic extra-ordinary transmission : testing the maintenance of optical frequency and phase via a frequency comb - Kim, Young-Jin (2018)
Frequency comb has shown remarkable potential in time/frequency metrology, atomic/molecular spectroscopy and precision LIDARs. It will create novel possibilities in nano-photonics and plasmonics; however, its interrelation with surface plasmons is unexplored despite the important role that plasmonics play in nonlinear spectroscopy and quantum optics through the manipulation of light in a subwavelength scale. We demonstrate that frequency comb can be transferred by plasmonic nanostructures without noticeable degradation of less than 6.51×10-19 in absolute position and 1 Hz in linewidth, which implies frequency comb’s potential applications in nanoplasmonic spectroscopy, quantum metrology and subwavelength photonic circuits.